TEX15 is an essential executor of MIWI2-directed transposon DNA methylation and silencing - Theresa Schöpp (Nature Portfolio, 2020)
The PIWI protein MIWI2 counteracts transposon activity by transcriptional silencing in the mammalian germline. Here, the authors show that TEX15 interacts with MIWI2 and is required for piRNA-directed methylation of transposable elements in male germ cells.